Development of a conceptual framework to integrate quality management system and risk management system - Samani, Mahmoud Asad (2016)
Proliferation in the number of Management Systems (MSs) necessary to manage an organization is an obvious fact and adopting an integration approach to deal with those MSs is an economic-wise manner. The need to create Integrated Management System (IMS) is the result of increase in the number of stakeholders and their respective Management System Standards (MSSs). The journal papers related to MSs‘ integration argue that in theory any two MSs or even more can potentially be integrated. In this research, it is shown that the attitudes and approaches behind the two important functionspecific MSSs developed by ISO Organization, i.e. Quality Management System (QMS) and Risk Management System (RMS) are largely similar and complementary. Hence,their integration is suggested and a conceptual framework for their integration is introduced. The main driver for such integration is to reduce the number of MSs in an organization and hence to decrease the number of resources employed. It is demonstrated that the integration of QMS and RMS will result in more significant background, cultural context, techniques, procedures and synergy to an organization. The conceptual integration model and the implementation strategy are two fundamental pillars for integration of any two or more MSs. Hence, various conceptual models are examined and a new model is developed and introduced to integrate RMS and QMS. The proposed conceptual framework is built upon a comprehensive review and analysis of authoritative field literatures and is named as the Risk-Based Quality Management System (RBQMS). The developed RBQMS framework is validated and verified in real case processes selected from service sector industry by means of a review questionnaire to collect the experts‘ opinion. The proposed RBQMS model was recognized and acknowledged by implementing organizations as an appropriate solution which enables organizations to mitigate and manage the threatening risks at large with easy understanding and using practical guidelines and templates.